A structural variant at ASIP associated with the darkness of hair coat is found in multiple zebu cattle populations - Trigo, Beatriz Batista [UNESP]; Alves, Natália Fonseca [UNESP]; Milanesi, Marco; Garcia, José Fernando [UNESP]; Terefe, Endashaw; Hanotte, Olivier; Tijjani, Abdulfatai; Utsunomiya, Yuri Tani [UNESP] (Wiley, 2023)
A structural variant (SV) in the agouti signaling protein gene (ASIP), namely ASIP-SV1, has been found to strongly correlate with the darkness of hair coat in specific regions of the body of bulls from the zebu (Bos indicus) Nellore breed. Here we visually analyzed the whole-genome sequence of zebu and taurine (Bos taurus) cattle to elucidate the extent of spread of ASIP-SV1 in different cattle populations. Of 216 sequences analyzed, 63 zebu (45.9%) and five taurine (6.3%) animals had at least one copy of ASIP-SV1. Four of the taurine animals presenting the SV were Romagnola cattle, a breed with history of zebu introgression. The remaining taurine animal was a Simmental, a breed frequently used in crossbreeding. These data provide evidence that ASIP-SV1 is commonly found in zebu populations, in addition to taurine animals with zebu admixture.
Keywords: agouti; coat color; introgression; taurine; zebu